Fetuin-A is a HIF target that safeguards tissue integrity during hypoxic stress - Stefan Rudloff (Nature Portfolio, 2021)
Intrauterine growth restriction is associated with increased risk for chronic diseases in adults. Here the authors identify fetuin-A as a HIF target gene and describe its protective role in the kidney, counteracting disease mechanisms such as calcification, macrophage polarization, and fibrosis.